PENGARUH CITRA MEREK, KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN DENGAN MEMPERHATIKAN STRATEGI BERSAING SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen Pegipegi.Com) - Kurniyawati, Renny (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2021)
This study is to determine the effect of brand image, service quality and promotion on customer satisfaction by paying attention to competitive strategies as an intervening variable. The object of this research is consumers from Pegipegi.com who have purchased tickets at Pegipegi.com. This research was conducted on 210 respondents using a quantitative descriptive approach. Therefore, the data analysis used is statistical analysis with Output processing software with SPSS 23, 2020 and primary data is processed using Smart-PLS, 2020. The results of this study indicate that the t test (bootstrapping) is the independent variable of brand image, service quality, and promotion has a positive and significant effect on the intervening and dependent variables, namely competitive strategies and customer satisfaction at Pegipegi.com.